Nicolau syndrome: A case of ischemic necrosis after subcutaneous immunotherapy - Joyce Kim, MD; Tim Kaddis, MD; Spencer Boyle, MD; Sandeep Gupta, MD; Vivian Wang, MD; Joseph Yusin, MD (Journal of Allergy and Clinical Immunology: Global)
A rare injection site reaction known as Nicolau syndrome can occur in patients receiving subcutaneous immunotherapy. This syndrome has been reported only a handful of times in the literature related to subcutaneous immunotherapy.